2013
DOI: 10.1016/j.intmar.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Thinking or Feeling the Risk in Online Auctions: The Effects of Priming Auction Outcomes and the Dual System on Risk Perception and Amount Bid

Abstract: The present research sheds new light on the antecedents and outcomes of bidders’ perceived risk. It examines the role of the two-system model in the context of activating the potential to either win or lose an online auction. This study demonstrates that when a bidder's affective system is primed, concern about losing the item is greater and ultimately the bid amount is higher when the bidder expects to lose rather than win. Conversely, when the cognitive system is primed, the anticipated goals of winning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Because insight can be divided into cognitive and affective components, only when individuals consider both of these two elements can they gain a full understanding of insight (Gick & Lockhart, ). Specifically, outcome‐oriented thinking is in line with cognitive system, whereas process‐oriented thinking matches the cognitive style of affective system (Steinhart, Kamins, & Mazursky, ), and the difference‐insight may be aroused when the cognitive outcome is not in line with affective process during social comparison. Dynamic inconsistencies can arise as in unexpected utility when process deviates from outcome (Trautmann, ).…”
Section: Research Hypothesismentioning
confidence: 99%
“…Because insight can be divided into cognitive and affective components, only when individuals consider both of these two elements can they gain a full understanding of insight (Gick & Lockhart, ). Specifically, outcome‐oriented thinking is in line with cognitive system, whereas process‐oriented thinking matches the cognitive style of affective system (Steinhart, Kamins, & Mazursky, ), and the difference‐insight may be aroused when the cognitive outcome is not in line with affective process during social comparison. Dynamic inconsistencies can arise as in unexpected utility when process deviates from outcome (Trautmann, ).…”
Section: Research Hypothesismentioning
confidence: 99%
“…Despite the enormous projections of growth of online payment systems, they have not achieved the expectations regarding level of performance and diffusion for the most part because of issues of risk/security (Hong, Zulkiffli, and Hamsani 2016;Linck, Pousttchi, and Wiedemann 2006;Steinhart et al 2013;Suki and Suki 2017;Tsiakis and Sthephanides 2005;Xu and Riedl 2011), trust (Chen et al 2016) and complexity of use (Chou, Lee, and Chung 2004). Recent research in fact concludes that perceived risk and security, together with product involvement and consumer characteristics, could be the most important determinants of use of e-payment systems (Faqih 2016;Kim, Mirusmonov, and Lee 2010;Kim et al 2010).…”
Section: Online Payment Systemsmentioning
confidence: 99%
“…In the following, we focus particularly on the role of emotions in electronic auctions, a domain of electronic commerce where affective processes related to social interactions have been found to play an important role in consumer behavior (Ariely and Simonson 2003;Ding et al 2005;Ku, Malhotra, and Murnighan 2005;Steinhart et al 2013). In particular, emotions have been found to be "an integral component of a bidder's decision state and bidding strategy" (Ding et al 2005, p. 363).…”
Section: Emotional Biddingmentioning
confidence: 99%
“…In addition to integral emotions, also incidental emotions, i.e., emotions not directly related to the auction, can have an impact on bidding behavior. Steinhart et al (2013) demonstrated that textual priming has a significant impact on bidding behavior. When bidders' affective system was primed, bidders were more concerned with losing the auction and thus placed higher bids.…”
Section: Emotional Biddingmentioning
confidence: 99%